Shame Mediates the Relationship Between Negative Trauma Attributions and Posttraumatic Stress Disorder (PTSD) Symptoms in a Trauma Exposed Sample - Rebecca Seah; David Berle (Clinical Psychology in Europe, 2022)
[Background] Theoretical models of self-conscious emotions indicate that shame is elicited through internal, stable, and global causal attributions of the precipitating event. The current study aimed to investigate whether these negative attributions are related to trauma-related shame and PTSD symptom severity. [Method] A total of 658 participants aged 18 to 89 (M = 33.42; SD = 12.17) with a history of trauma exposure completed a range of self-report measures assessing trauma exposure, negative trauma-related attributions, shame, and PTSD symptoms. [Results] Higher levels of internal, stable, and global trauma-related attributions were significantly associated with shame and PTSD. Shame mediated the association between trauma-related attributions and PTSD symptom severity, even after controlling for the effects of number of trauma exposures, worst index trauma and depression. [Conclusions] The present results suggest that negative attributions are a critical cognitive component related to shame and in turn, PTSD symptom severity. Future research should aim to replicate these findings in a clinical sample and extend these findings using prospective designs.